2014
DOI: 10.1590/s0100-83582014000300003
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of sourgrass based on days or thermal units

Abstract: -This work was carried out with the objective of evaluating growth and development of sourgrass (Digitaris insularis) based on days or thermal units (growing degree days -GDD). Two independent trials were developed aiming to quantify the species' phenological development and total dry matter accumulation in increasing or decreasing photoperiod conditions. Plants were grown in 4 L plastic pots, filled with commercial substrate, adequately fertilized. In each trial, nine growth evaluations were carried out, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
8
0
1
Order By: Relevance
“…These results corroborate those obtained by Marques et al (2014) in D. insularis plants without distinction of glyphosate resistance. However, in the study conducted by Machado et al (2006), a slow growth rate was observed until 45 DAE, and the maximum accumulated total dry matter of D. insularis was 30.7 g per plant at 105 DAE.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results corroborate those obtained by Marques et al (2014) in D. insularis plants without distinction of glyphosate resistance. However, in the study conducted by Machado et al (2006), a slow growth rate was observed until 45 DAE, and the maximum accumulated total dry matter of D. insularis was 30.7 g per plant at 105 DAE.…”
Section: Resultssupporting
confidence: 91%
“…These models can be used to understand the influence of biological, ecological, genetic and management factors on the likelihood of selection for glyphosate-resistant weeds in agricultural lands and in the development of strategies to mitigate these risks by means of simulation models (Neve, 2008;Marques et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The D. insularis species is a perennial plant that is highlighted by the formation of rhizome and clumps, with slow initial growth and posterior exponential dry matter accumulation (Machado et al, 2008;Carvalho et al, 2013;Marques et al, 2014). Such factors is related to its aggressiveness as a weed species and may provide high competitiveness to the species for natural resources, among them, nutrients present in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Assim sendo, ao menos em teoria, uma planta é capaz de crescer sem, necessariamente, desenvolver-se e vice-versa (MARQUES et al, 2014;MACHADO et al, 2014). Assim sendo, para estimar o crescimento e o desenvolvimento vegetal, além da descrição das fases fenológicas, torna-se fundamental a mensuração da massa de matéria seca das diferentes estruturas da planta (ANDRADE et al, 2009;TAKANO et al, 2016).…”
Section: Introductionunclassified